2005
DOI: 10.1007/s00705-005-0495-z
|View full text |Cite
|
Sign up to set email alerts
|

Two unique US isolates of Pepino mosaic virus from a limited source of pooled tomato tissue are distinct from a third (European-like) US isolate

Abstract: Three strains of Pepino mosaic virus (PepMV) found in the US have been cloned and sequenced by RT-PCR using total RNA from infected tissue as template, and degenerate potexvirus- and PepMV species- and isolate-specific primers. Despite limited source material, the complete nucleotide sequences (6413 and 6410 nts, respectively) of two isolates, PepMV-US1 and PepMV-US2, were obtained and analyzed using total RNA from less than 0.2 g of a pooled infected tomato leaf sample from Arizona. Sequence of the 3'-end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 19 publications
1
55
0
6
Order By: Relevance
“…Damage and economic losses caused by PepMV vary greatly and can at least partially be attributed to the differential symptomatology caused by different PepMV isolates (Hanssen et al, 2009(Hanssen et al, , 2010a. Currently, four PepMV genotypes are distinguished: the Peruvian genotype (LP), which was first isolated from Solanum peruvianum and is similar to the original pepino (S. muricatum) isolate (Ló pez et al, 2005;Pagán et al, 2006); the European tomato genotype (EU), which was first reported in greenhouse tomato production in Europe (Mumford and Metcalfe, 2001;Aguilar et al, 2002;Cotillon et al, 2002;Verhoeven et al, 2003;Pagán et al, 2006); the CH2 genotype, which was first isolated from tomato seeds from Chile (Ling, 2007); and the US1 genotype, which was first described in the United States (Maroon-Lango et al, 2005). In recent years, the CH2 genotype has largely replaced the EU genotype in commercial tomato production in several European countries (Hanssen et al, 2008;Gó mez et al, 2009).…”
mentioning
confidence: 91%
“…Damage and economic losses caused by PepMV vary greatly and can at least partially be attributed to the differential symptomatology caused by different PepMV isolates (Hanssen et al, 2009(Hanssen et al, , 2010a. Currently, four PepMV genotypes are distinguished: the Peruvian genotype (LP), which was first isolated from Solanum peruvianum and is similar to the original pepino (S. muricatum) isolate (Ló pez et al, 2005;Pagán et al, 2006); the European tomato genotype (EU), which was first reported in greenhouse tomato production in Europe (Mumford and Metcalfe, 2001;Aguilar et al, 2002;Cotillon et al, 2002;Verhoeven et al, 2003;Pagán et al, 2006); the CH2 genotype, which was first isolated from tomato seeds from Chile (Ling, 2007); and the US1 genotype, which was first described in the United States (Maroon-Lango et al, 2005). In recent years, the CH2 genotype has largely replaced the EU genotype in commercial tomato production in several European countries (Hanssen et al, 2008;Gó mez et al, 2009).…”
mentioning
confidence: 91%
“…En el gen del TGBp1 se observa un (región intergénica entre el TGB y la ORF5), se encuentra la última región del genoma del virus, que codifica para la proteína de la cápside (CP) de 25 kDa, y en la cual se encuentra la secuencia conservada de naturaleza antifática 5´KFAAFDFFDGVT 3´, responsable posiblemente de la unión del RNA viral a la CP mediante interacciones hidrofóbicas. En su extremo 3´, tras una serie de nucleótidos que no se traducen (3´UTR), se encuentra la cola poli-A (Aguilar et al, 2002;Cotillon et al, 2002;Maroon-Lango et al, 2005;Ling, 2007;Hasiów et al, 2007).…”
Section: Estructura De La Partícula Viral Y Organización Genómicaunclassified
“…Con respecto a la asociación entre la variabilidad genética y sintomatológica, no se conoce en la actualidad qué zona del genoma la induce o cuáles son los nucleótidos y aminoácidos determinantes responsables de las características biológicas de los aislados (Maroon-Lango et al, 2005;Pagán et al, 2006;Hanssen et al, 2008;Hasiów-Jarosweska et al, 2009a). Sin embargo, se ha demostrado que la coinfección en algunas plantas de los genotipos EU y CH2 genera una mayor agresividad en los síntomas de PepMV observados (Hanssen et al, 2008), lo que se asocia a una mayor acumulación viral frente a las infecciones simples (Hanssen et al, 2009b …”
Section: Variabilidad Genéticaunclassified
See 2 more Smart Citations